Fundamental Fermion Interactions via Vector Bosons of Unified SU(2)⊗SU(4) Gauge Fields - Marsch, Eckart; Narita, Yasuhito (Frontiers in Physics, 2016)
Employing the fermion unification model based on the intrinsic SU(8) symmetry of a generalized Dirac equation, we discuss the fundamental interactions under the SU(8)=SU(2)SU(4) symmetry group. The physics involved can describe all fermions, the leptons (electron and neutrino), and the coloured up and down quarks of the first generation in the standard model (SM) by a complex SU(8) octet of Dirac spinor fields. The fermion interactions are found to be mediated by the unified SU(4) and SU(2) vector gauge boson fields, which include the photon, the gluons, and the bosons Z and W as well known from the SM, but also comprise new ones, namely three coloured X bosons carrying a fractional hypercharge of ±4/3 and transmuting leptons into quarks and vice versa. The full covariant derivative of the model is derived and discussed. The Higgs mechanism gives mass to the Z and W bosons, but also permits one to derive the mass of the coloured X boson, for which depending on the choice of the values of the coupling constant, the estimates are 35 GeV or 156 GeV, values that are well within reach of the LHC. The scalar Higgs field can also lend masses to the fermions and fix their physical values for given appropriate coupling constants to that field.